Digital Holographic Display System with Large Screen Based on Viewing Window Movement for 3D Video Service - Park, Minsik; Chae, Byung Gyu; Kim, Hyun‐Eui; Hahn, Joonku; Kim, Hwi; Park, Cheong Hee; Moon, Kyungae; Kim, Jinwoong (ETRI journal, 2014)
A holographic display system with a 22‐inch LCD panel is developed to provide a wide viewing angle and large holographic 3D image. It is realized by steering a narrow viewing window resulting from a very large pixel pitch compared to the wave length of the laser light. Point light sources and a lens array make it possible to arbitrarily control the position of the viewing window for a moving observer. The holographic display provides both eyes of the observer with a holographic 3D image using two vertically placed LCD panels and a beam splitter to support the holographic stereogram.